Organizational Interoperability: Strengthening Collaboration in Systems of Information Systems - Proencia, Edlane Cristine dos Santos; Mascarenhas, Ana Patrícia Fontes Magalhães; Mane, Babacar; Claro, Daniela Barreiro; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248363, 2026)
Research Context: Collaborative System of Information Systems (SoIS) involve multiple independent organizations that must interact dynamically, without centralized control, to achieve both collective and individual objectives. Organizational interoperability is crucial in this context but still lacks adequate solutions when participants frequently join or leave the collaboration. Scientific and/or Practical Problem: Current BPM and SOA approaches were designed for static intra or inter-organizational contexts and do not handle the dynamic nature of SoIS. This limitation creates difficulties in maintaining process continuity when participants enter or exit, compromising global objectives. Proposed Solution and/or Analysis: This research proposes a solution for organizational interoperability in collaborative SoIS comprising a metamodel and a semi-automated simulation environment. The metamodel specifies key concepts, properties, and relationships for modeling collaborative SoIS, while the simulation environment enables the specification and enactment of model instances according to the metamodel. Related IS Theory: Research on organizational interoperability is associated with organizational information processing theory and the complexity of information systems. Research Method: The Design Science Research (DSR) approach was adopted, following the steps of investigation, design, validation, implementation and evaluation. Summary of Results: The metamodel was applied in an e-commerce scenario, showing it to be consistent, expressive, and able to represent domain concepts through models adhering to its rules and structure. The simulation environment executed these models, enabling analysis of participant entry and exit dynamics and demonstrating process continuity despite organizational changes. Contributions and Impact to IS area: The approach provide both a conceptual foundation and a means for analyzing and improving collaboration in dynamic interorganizational contexts. The impact lies in enabling more resilient and adaptive SoIS, capable of maintaining continuity and interoperability even under frequent organizational changes.